Novel Analysis on the Impact of FinTech Developments for Monetary Policy: The Case of Türkiye - Kömürcüoğlu, Ömer Faruk; Akyazi, Haydar (Ekonomika, 2024)
One of the most noteworthy benefits that new technological opportunities bring to economies is Financial technologies (FinTech), which makes it easier for financial services to be cheap, fast, and accessible, especially by creating more digital payment services. This high rate of digitalization in payment services changes the liquidity preferences of economic agents daily and may affect the demand for central bank money. However, the prerequisite for the central bank to carry out monetary policy and be effective is accurately predicting the demand for its own money. Therefore, the developments in FinTech, in the last decade, are among the most attention-grabbing issues for demand in money, as well as being in the leading position for central banks, which followed intimately. In this context, the aim of this study is to reveal the impacts of developments in FinTech on monetary policy for Türkiye’s real money demand. For this purpose, in order to represent the developments in financial technologies, The FinTech index, which is formed for the first time in the relevant economy using the PCA method over the period 2012:Q1–2021:Q4, is included in the model where national income, interest rate, exchange rate, and inflation are explanatory variables. Results from the ARDL approach show that FinTech developments and demand for money are co-integrated, and also an increase in FinTech reduces money demand both in the short and long-run. The causality analysis handled with the Toda-Yamamoto approach has revealed the existence of a bidirectional causality relationship between FinTech and money demand. Accordingly, Fintech developments in Türkiye have a huge potential to shape economic agents’ liquidity preferences. To maintain the effectiveness of monetary policy, the policymakers in the central bank should closely follow FinTech developments and supervise and regulate activities that will create an alternative to its currency.
Keywords: Financial Technology; Monetary policy; Türkiye; FinTech; ARDL